Strategi Pertahanan Indonesia dalam Menghadapi Ancaman Militer dan Non Militer Melalui Prespektif Ekonomi Pertahanan - Yudi Sutrasna (Syntax Literate, 2023)
Advances in science and technology are one of the factors that can pose military and non-military threats. For this reason, the study of Indonesian defense is important for the academic and policy community. Countries tend to accumulate weapons or ally with big powers to maintain national security. This study aims to analyze the defense strategy adopted by Indonesia in facing military and non-military threats. Qualitative research methods with a phenomenological approach. This study concludes that national defense is the duty and responsibility of all elements of the nation, so a critical and scientific way of thinking is needed to build national defense through enriching the scientific repertoire of defense management. In addition, the defense economic perspective is an alternative that can be used as a defense strategy for Indonesia in facing various threats.